Sleeve fracture of the patella in a child - Ahmad Hata, Rasit (Malaysian Medical Association, 2004)
Sleeve fracture of the inferior pole of the patella is a rare and distinctive fracture in children with few published reports. These fractures are frequently misdiagnosed and neglected. We highlight a case of a neglected and misdiagnosed sleeve fracture of the patella in an eleven-year-old boy. This was initially diagnosed as an avulsion fracture of the tibial tubercle. A good outcome was achieved after open reduction and internal fixation.